An alternative framework for the technological and transaction firm models. (1st January 2001) - Geursen, Gus M.; Rivers, George
Economics, management and business have for some time questioned our perceptions about what is a "firm". The need to comprehend this question is paramount to understanding the functioning not only of our firms but also of our economic systems, both at a micro and macro level. Neoclassical theorists have generally assumed that the distribution of resources in an economy is dependent directly upon the price and markets. Notwithstanding this, the questions remain why do firms or organisations exist, and what is the nature of their mechanisms? A significant limitation in economic discussion is that it considers the firm as consisting of a horizontal set of inputs and outputs but fails to recognise that there are vertical divisions of these sets among which trade-offs occur. Contextual discussion of these vertical divisions is the focus of this paper. A new framework is developed to enable the identification and analysis of those particular aspects that make the firm function.